A Study of Cracks on Double Storey Houses - Xin Yee, Low; Zainal, Rozlin (Research in Management of Technology and Business, 2021)
Cracking is the common defect found on any types of building or house nowadays. This is the serious problem caused by different kinds of causes. The objectives of this research are to identify the types of cracks occur on double-storey houses, to investigate the significant causes of cracks occur on double-storey houses and to investigate the solutions for cracks on double-storey houses. Data collecting was based on the qualitative method. The observation was conducted at the most affected double-storey houses at Taman Lapangan Indah, Ipoh, Perak. Meanwhile, a total of five contractors from Ipoh, Perak were interviewed. The data was analysed using the narrative analysis technique. The main findings indicated that plaster crack, column crack, beam crack, slab crack, hairline crack, and wall surface crack are types of cracks occur on double-storey houses. Nine significant causes of cracks occur on double-storey houses have been confirmed including poor structural design, mixture of ready mixed concrete, change in weather, level of moisture content, poor quality of materials, poor mixture of concrete, quality of cement, poor mortar mix and poor workmanship. The results also showed that crystalline cement, gravity filling, additional reinforcement, re-plaster and surface treatment are the solutions to these issues. Based on these findings, this research suggested that different types and causes of cracks should be investigated earlier and appropriate solutions are needed to adopt immediately. In conclusion, this research mainly to increase alertness among owner of house related on types, causes and solutions of cracks.